2007
DOI: 10.1158/1535-7163.mct-07-0217
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol causes G0-G1 phase cell cycle arrest in human prostate cancer cells in association with suppression of retinoblastoma protein level/phosphorylation and inhibition of E2F1 transcriptional activity

Abstract: The present study was undertaken to gain insights into the mechanism of cell cycle arrest caused by honokiol, a constituent of oriental herb Magnolia officinalis. The honokiol treatment decreased the viability of PC-3 and LNCaP human prostate cancer cells in a concentrationand time-dependent manner, which correlated with G 0 -G 1 phase cell cycle arrest. The honokiol-mediated cell cycle arrest was associated with a decrease in protein levels of cyclin D1, cyclin-dependent kinase 4 (Cdk4), Cdk6, and/or cyclin E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
88
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 43 publications
10
88
1
Order By: Relevance
“…Our results are consistent with those of other reports showing that over 40 mM honokiol decreases the viability of prostate cancer cells but has no effect at 20 mM. 22) The fact that the honokiol treatment at concentrations lower than 20 mM did not cause cell death indicates that the increased expression of ABCA1 due to honokiol is not a cause of cell death.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with those of other reports showing that over 40 mM honokiol decreases the viability of prostate cancer cells but has no effect at 20 mM. 22) The fact that the honokiol treatment at concentrations lower than 20 mM did not cause cell death indicates that the increased expression of ABCA1 due to honokiol is not a cause of cell death.…”
Section: Resultssupporting
confidence: 93%
“…Given that ABCA1 expression is upregulated during apoptosis in human fibroblasts, 21) and honokiol induces apoptosis in tumor cells, 22) we also examined apoptotic processes by TUNEL assay, an indicator of cell death accompanied by DNA fragmentation, in U251-MG cells following the treatment with indicated concentrations (0, 10, 20, 80 mM) of honokiol. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that honokiol treatment decreases viability of LNCaP (androgen receptor positive and wild-type p53) and PC-3 (androgen receptor null and p53 null) human prostate cancer cells at 20 to 60 Amol/L concentrations as judged by trypan blue dye exclusion assay (25). In the present study, we used the same cell lines to test whether honokiol promotes apoptosis.…”
Section: Resultsmentioning
confidence: 93%
“…In human prostate cancer, honokiol activated p21 (PC-3 and LNCaP) and p53 protein expression (LNCaP; ref. 36).…”
Section: P53 and Its Family Members Pathwaymentioning
confidence: 99%